Copy trading - Apesteguia, Jose; Oechssler, Joerg; Weidenholzer, Simon (Discussion paper series, 2018)
Abstract: Copy trading allows traders in social networks to receive information on the success of other agents in financial markets and to directly copy their trades. Internet platforms like eToro, ZuluTrade, and Tradeo have attracted millions of users in recent years. The present paper studies the implications of copy trading for the risk taking of investors. Implementing an experimental financial asset market, we show that providing information on the success of others leads to a significant increase in risk taking of subjects. This increase in risk taking is even larger when subjects are provided with the option to directly copy others. We conclude that copy trading reduces ex-ante welfare, and leads to excessive risk taking.
Key words: Copy trading, Financial markets, Social networks, Imitation, Experiment; JEL codes: C91, D81, G12, G20, G41
Keywords: Graue Literatur